Performance evaluation of ecological governance based on public value and cost structure: empirical evidence from China - Ma, Bei; Liu, Shuang; Qiu, Rongshan (Transformations In Business & Economics, 2026)
Based on the framework of public value and cost structure, combined with the characteristics of China’s ecological policies, this study constructs an evaluation index system from four dimensions: fairness, efficiency, participation, and sustainability. Weights of indicators are determined using the analytic hierarchy process and the entropy method. Furthermore, the public value performance model, cost structure performance model, and their integrated model are applied to evaluate China’s ecological governance performance from 2015 to 2024. Results show that over the decade, China’s ecological governance performance has improved from "average" to "good," with all four dimensions exhibiting an upward trend. However, the overall level remains relatively low. Spatially, performance has improved across all regions, with the eastern region outperforming the northeastern, centrai, and western regions. The findings indicate that despite significant achievements and continuous growth in the performance index of China’s ecological governance, deficiencies in fairness, participation, efficiency, and sustainability have constrained further improvement. Therefore, additional effort is needed to improve the ecological compensation system; stimulate the enthusiasm of multiple subjects for participation; clarify the rights, responsibilities, and interests of all parties; and establish a multigovernance and collaborative governance mechanism . This study clarifies the dynamic evolution characteristics and care dilemmas of China’s ecological governance performance. Therefore, it provides support for promoting the green and low-carbon transformation of the economy and realizing high-quality development characterized by the coordinated coupling of economic society and ecology.